Organo–organic and organo–mineral interfaces in soil at the nanometer scale - Angela R. Possinger (Nature Portfolio, 2020)
Historically it has been maintained that soil organic carbon (SOC) is stabilized through interactions with mineral interfaces. Here the authors use cryo-electron microscopy and spectroscopy to show that SOC interactions can also occur between organic forms in patchy, disordered structure.